Tofersen and other antisense oligonucleotides in ALS - Albert Ludolph; Maximilian Wiesenfarth (Therapeutic Advances in Neurological Disorders)
The advent of antisense oligonucleotide (ASO) therapies in neurodegenerative disorders is associated with enormous hope. Nusinersen treatment was a breakthrough intervention in the recessive disease spinal muscular atrophy, and superoxide dismutase 1 (SOD1) amyotrophic lateral sclerosis (ALS) seems to be the paradigm disease in dominant degenerative diseases. The results of treatment with the ASO tofersen in SOD1-ALS show that the drug has a convincing beneficial effect on ALS caused by SOD1 mutations, that preclinical studies in rodents predicted the therapeutic effect in the human disease, and that clinical efficacy is associated with a specific sequence of effects of the drug on mechanistic and degenerative biomarkers and, subsequently, functional outcomes such as weight stabilization and ALSFRS-R. Therefore, the enthusiasm seems to be justified; but this should be followed by an attempt to obtain further insights with the goal to improve this therapy. In particular, the following issues are only partially resolved: Which mechanisms are responsible for the clinical effect following the downregulation of SOD1 protein by ASOs? Is long-term downregulation of SOD1 function associated with side effects? Is there an autoimmune response caused by this and other ASO? Is prevention of SOD1-associated ALS possible?